PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN MODERASI DISIPLIN KERJA PADA PT. BANGUN ARTA HUTAMA - Moehammad Budi Widajanto (Universitas 17 Agustus 1945 Surabaya, 2018)
The aims of this study is to examine whether organizational culture influencesemployee performance, and examines work discipline moderates the influencebetween organizational culture on employee performance. The population in thisstudy were all employees of PT. Build Arta Hutama as many as 133 people. Basedon calculations with Slovin formula, the sample is taken as many as 100 samples.Analysis techniques use moderated regression analysis. Based on the results of thestudy it can be concluded that organizational culture influences the performanceof employees of PT. Build Arta Hutama. Work discipline moderates the influencebetween organizational culture on the performance of employees of PT. BuildArta Hutama with the form of